Determination of macro- and micronutrients in plant leaves by high-resolution continuum source flame atomic absorption spectrometry combining instrumental and sample preparation strategies - Oliveira, Silvana R. [UNESP]; Gomes Neto, José Anchieta [UNESP]; Nobrega, Joaquim A.; Jones, Bradley T. (Pergamon-Elsevier B.V. Ltd, 2010)
A method for determination of B, Ca, Cu, Fe, K, Mg, Mn, Mo, P. S and Zn in plant tissues by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS) is proposed. This method is based on special features of HR-CS-AAS, such as side pixel registration, wavelength integrated absorbance, and molecular absorption bands, for determining macro- and micronutrients in foliar analysis without requiring several different strategies for sample preparation and adjustment of the analytes concentration ranges. Plant samples were analyzed and results for certified materials were in agreement at a 95% confidence level (paired t-test) with reference values. Recoveries of analytes added to plant digests varied within the 82-112% interval. Relative standard deviations (n = 12) were lower than or equal to 5.7% for all analytes in all concentration ranges. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: High-resolution continuum source flame atomic absorption spectrometry; Foliar diagnosis; Macronutrients; Micronutrients